Advances in Physical Ergonomics and Human Factors Proceedings of the AHFE 2016 International Conference on Physical Ergonomics and Human Factors, July 27-31, 2016, Walt Disney World®, Florida, USA - Goonetilleke, Ravindra; Karwowski, Waldemar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book reports on the state of the art in physical ergonomics and is concerned with the design of products, process, services, and work systems to assure their productive, safe, and satisfying use by people. With focus on the human body's responses to physical and physiological work demands, repetitive strain injuries from repetition, vibration, force, and posture are the most common types of issues examined, along with their design implications. The book explores a wide range of topics in physical ergonomics, which includes the consequences of repetitive motion, materials handling, workplace safety, and usability in the use of portable devices, design, working postures, and the work environment. Mastering physical ergonomics and safety engineering concepts is fundamental to the creation of products and systems that people are able to use, as well as the avoidance of stresses and minimization of the risk of accidents. Based on the AHFE 2016 International Conference on Physical Ergonomics & Human Factors, held on July 27-31, 2016 in Walt Disney World®, Florida, USA, the book provides readers with a comprehensive view of the current challenges in Physical Ergonomics, which are a critical aspect in the design of any human-centered technological system, and factors influencing human performance.
Prevention of Work-Related Musculoskeletal Disorders -- Physical Ergonomics in Design -- Biomechanical Evaluations -- Clothing and Personal Protective Equipment -- Product Design -- Anthropometry -- Performance and Productivity -- Wearables and Innovative Interfaces -- Safety and Health -- Behavioral Ergonomics -- Behavioral Ergonomics.
Keywords: Computational intelligence; Occupational health services; Security systems; Psychology, Experimental; User interfaces (Computer systems).; Human-computer interaction; Computational Intelligence; Occupational Health; Security Science and Technology; Experimental Psychology; User Interfaces and Human Computer Interaction